Performance and stability of semitransparent OPVs for building integration: A benchmarking analysis. (July 2019) - Chemisana, D.; Moreno, A.; Polo, M.; Aranda, C.; Riverola, A.; Ortega, E.; Lamnatou, Chr.; Domènech, A.; Blanco, G.; Cot, A.
Abstract: Semitransparent (ST) organic photovoltaics (OPVs) are demonstrating great potential for building integration applications, especially in windows. For that purpose, ST-OPVs should achieve adequate transparency and performance stability. In this regard, the present research deals with the experimental performance of three different building-integrated ST-OPV technologies (technology A: developed in the frame of the present study; technologies B and C: commercial modules). More specifically, spectral transmittance and electrical measurements have been conducted in order to determine the characteristics of the modules for building integration and electricity generation purposes. Results regarding the transmittance reveal that technology A outperforms technologies B and C. The stability analysis of the modules verifies that module C is the most stable one with almost no decrease (3.6%) in the power conversion efficiency (PCE). Furthermore, the PCE of technology B is slightly higher than in the case of technology C, which experiences a PCE degradation of about 10–15% over the whole time period. Finally, technology A presents a 20% reduction in PCE at around 500 h.